2019
DOI: 10.1096/fj.201801338rrr
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐3 deficiency slows cyst enlargement in experimental mouse models of autosomal dominant polycystic kidney disease

Abstract: Human autosomal dominant polycystic kidney disease (ADPKD) is characterized by bilateral renal cysts that lead to a decline in kidney function. Previous studies reported aquaporin (AQP)‐3 expression in cysts derived from collecting ducts in ADPKD. To study the role of AQP3 in cyst development, we generated 2 polycystic kidney disease (PKD) mouse models: kidney‐specific Pkd1 knockout mice and inducible Pkd1 knockout mice, each without and with AQP3 deletion. In both models, kidney sizes and cyst indexes were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…23 Wang and colleagues also found that AQP3 protein levels correlated with HIF-1α in a matrixgrown Madin-Darby canine kidney cyst model. 60 Therefore, we investigated whether changes in AQP3 expression affected hypoxic HCC cell sensitivity to sorafenib. We found that hypoxic cells transfected with lentivirus expressing AQP3 were less sensitive to sorafenib-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Wang and colleagues also found that AQP3 protein levels correlated with HIF-1α in a matrixgrown Madin-Darby canine kidney cyst model. 60 Therefore, we investigated whether changes in AQP3 expression affected hypoxic HCC cell sensitivity to sorafenib. We found that hypoxic cells transfected with lentivirus expressing AQP3 were less sensitive to sorafenib-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] AQP3's role in tumor progression, prognosis, and treatment has recently garnered attention. In addition to promoting tumor progression and metastasis, [24][25][26][27][28] AQP3 is involved in drug resistance in various malignant tumors. 29,30 AQP3 knockdown or knockout studies have demonstrated its role in various tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…AQP3-deficient kidneys of pkd1-null mice exhibit significantly reduced ATP content, increased phosphorylated (p-)AMP-activated protein kinase (AMPK), and decreased p-ERK and p-mTOR in parallel with reduced kidney size and cyst indexes. These findings imply that AQP3 may also participate in renal cyst enlargement and, thus, may be a potential drug target for ADPKD (93). In addition, recent studies have revealed that a single nucleotide mutation of the AQP11 gene and AQP11 gene knockout have disruptive PC-1 trafficking to the plasma membrane and consequently develop polycystic kidneys (74,84).…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 96%
“…Approximately 400 MDCK cells were suspended in 0.4 mL of ice-cold MEM (Sigma-Aldrich, St. Louis, MO, USA) containing 2.9 mg/mL collagen (PureCol; Inamed Biomaterials, Fremont, CA, USA), 10 mM HEPES, 100 U/mL penicillin, and 100 μg/mL streptomycin (pH 7.4) in each well of a 24-well plate (Corning, NY, USA). Dulbecco’s modified Eagleʼs medium-F12 medium (DMEM-F12) containing 10% FBS and 10 μM FSK without or with GA monomers was added to each well and exchanged every 12 h. The relevant procedures were performed as previously described [ 20 ]. Micrographs of the cysts (≥30/group) were obtained with an inverted microscope (Nikon TE2000-S; Nikon Instruments, Melville, NY) on days 4, 6, 8, 10, and 12.…”
Section: Methodsmentioning
confidence: 99%